Measuring English language proficiency across subgroups: Using score equity assessment to evaluate test fairness. (April 2019) - Yoo, Hanwook; Manna, Venessa F.; Monfils, Lora F.; Oh, Hyeon-Joo
This study illustrates the use of score equity assessment (SEA) for evaluating the fairness of reported test scores from assessments intended for test takers from diverse cultural, linguistic, and educational backgrounds, using a workplace English proficiency test. Subgroups were defined by test-taker background characteristics that research has shown to be associated with performance on language tests. The characteristics studied included gender, age, educational background, language exposure, and previous experience with the assessment. Overall, the empirical results indicated that the statistical and psychometric methods used in producing test scores were not strongly influenced by the subgroups of test takers from which the scores were derived. This result provides evidence in support of the comparability and meaning of test scores across the various test-taker groups studied. This example may encourage language testing programs to incorporate SEA analyses to provide evidence to inform the validity and fairness of reported scores for all groups of test takers.